Hospital nurses' knowledge regarding older patients: a multicenter study - Christel T. A. J. Derks; Marjo M. G. M. Hutten - van den Elsen; Lysette J. Hakvoort; Mariëlle P. J. van Mersbergen; RENurse Consortium; Marieke J. Schuurmans; Jeroen Dikken (BMC, 2021)
Abstract Background Nursing care in hospitals increasingly involves older adults. A nursing workforce able to care for the ageing population is therefore critical for ensuring quality older adult care. Gaining insight in the knowledge and attitudes of nurses regarding older patients in the Netherlands is needed to develop and increase the impact of education- and quality improvement programs which can positively influence nurses' knowledge and attitudes regarding older patients. Methods A cross-sectional multicenter study was performed. Data was collected in ten tertiary medical teaching hospitals well spread across the Netherlands (89 wards, 2902 nurses). Knowledge levels were measured using the Knowledge about Older Patient-Quiz (KOP-Q), consisting of 30 true-false questions. Knowledge levels of registered nurses are compared with knowledge levels known from literature of first year nursing students; last year nursing students; nurses; and nurse specialist. Potential associated factors considered were: age; sex; education; experience; opinions and preferences. Opinion and preferences regarding working with older patients were measured by three questions: 1) which patient group nurses preferred to work with; 2) how nurses feel about the increase of older patients in the hospital; and 3) whether nurses find it difficult to care for older patients. Results From all wards, a representative sample of 1743 registered hospital nurses working on all 89 wards participated. On all wards, a large range in knowledge levels is observed between nurses, with 37% of nurses presenting knowledge levels comparable with nursing student and 31% of nurses presenting knowledge levels comparable with nurse specialists. Knowledge is related to age (p < .001), work experiences (p < .001), preparatory secondary education (p < .001) and nurses education level (p = .012). A minority (12.5%) prefers working with older patients and most nurses do not find it difficult. Conclusions This study shows that there is a large diversity in knowledge levels of Dutch hospital nurses in every hospital, on every ward. A majority of nurses demonstrate negative opinions and preferences. This implies that older patients admitted can receive different levels of quality of care on the same day as nurses with different knowledge levels provide care during the various shifts. Findings demonstrate an urgent need for education programs with themes regarding essential care for older patients in the Netherlands.